Capsicum Current Trends and Perspectives - Baylen Yllano, Orlex (IntechOpen, 2023)
Capsicum is among the most valuable crops in the world. Its rich history, diverse colors, textures, variable pungency, and health-promoting potential make it a desirable crop. Capsicum - Current Trends and Perspectives explores Capsicum biology, genetics, genomics, metabolic pathways, pharmacological properties, potential health benefits, and pathogens. It also discusses pest management strategies, breeding for higher productivity, and post-handling practices. Whether you are a student, researcher, teacher, nutritionist, food scientist, chef, farmer, producer, or simply a Capsicum enthusiast, this book is for you and will serve as your ultimate guide to current trends and perspectives on this highly versatile and beloved crop worldwide.